Mechanical analysis and material preparation of ultra-high-strength base asphalt pavement - TAN Bo; ZHENG Gang; LI Qing; XIE Enlian; LIU Jingshuang (河南理工大学学报. 自然科学版)
ObjectivesTo improve the structural performance of asphalt pavement and achieve low-carbon goals， an AC+ultra-high-strength base asphalt pavement structure is proposed to reduce the thickness of the asphalt pavement structurue.MethodsBisar software was used to analyze the mechanical response of the ultra-high-strength base pavement structure， proposing the design parameters for the asphalt pavement structure and ultra-high-strength base material. Orthogonal experimental design was then conducted to analyze the influence of silica fume， fly ash， and cement-sand ratio parameters on the mechanical properties of the ultra-high-strength base material. Range and variance analysis were performed to determine the optimal mix proportion. Finally， the bonding performance between asphalt layers and the ultra-high-strength base layer was evaluated through splitting tensile tests using five methods： spreading crushed stones， brushing grooves， epoxy resin， spraying modified asphalt， and rubber asphalt.ResultsThe results show that when the thickness of the ultra-high-strength base is 0.08 m， with an elastic modulus of 40 GPa， the total thickness of the structure is 0.52 m. The fatigue cracking life of the asphalt mixture and inorganic binder layers in the ultra-high-strength base asphalt pavement is higher than that of a conventional asphalt pavement with a total thickness of 0.74 m. The optimal mix ratio for the ultra-high-strength base material is 13% silica fume， 11% fly ash， a cement-sand ratio of 0.8， and a water-cement ratio of 0.25. The splitting tensile strength tests indicate that epoxy resin provides the best bonding， followed by crushed stone， and rubber asphalt provides the weakest bonding.ConclusionsUnder reduced pavement thickness， the AC+ ultra-high-strength base asphalt pavement performs better than conventional asphalt pavement. This study proposes a low-carbon and cost-effective asphalt pavement structure and material preparation method. The interlayer bonding performance between the asphalt surface layer and ultra-high-strength base layer is analyzed， and the use of spreading crushed stones is recommended， providing a new feasible approach for composite asphalt pavement.